Nephrotoxicity in a Patient With Inadequate Pain Control: Potential Role of Pharmacogenetic Testing for Cytochrome P450 2D6 and Apolipoprotein L1 - Tillman, Emma M.; Skaar, Todd C.; Eadon, Michael T. (Frontiers in Pharmacology, 2020)
A case is presented which demonstrates the perils of opioid inefficacy and how pharmacogenomic testing may have prevented NSAID-induced nephrotoxicity and progression to chronic kidney disease (CKD). A 62 year-old female with back pain was treated with tramadol and hydrocodone; however, neither proved effective. Consequently, to control her pain, she resorted to cocaine, marijuana, and high dose nonsteroidal anti-inflammatory drugs (NSAIDs). She eventually developed CKD. To identify CKD contributors, she underwent genotyping for Apolipoprotein L1 (APOL1), a known risk factor of CKD, as well as relevant pharmacogenomic genes. Her APOL1 genotype was *G1(GM)/*G1(GM), placing her at increased risk of CKD progression. Her CYP2D6 genotype was *5/*17, consistent with intermediate metabolism, making opioid drugs reliant on CYP2D6 activation, such as tramadol and hydrocodone, relatively ineffective in this patient. Thus, this patient was at genetic risk for CKD and reduced opioid efficacy. We conclude that this genetic combination likely contributed to opioid inefficacy and the eventual progression to CKD.